Sistem Perancangan dan Pelacakan Menggunakan Antena Tracking Sistem Model Dazel 4.5 M - Stevani Rika Natalia M (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
This technology is known as VSAT (Very Small Aperture Terminal). VSAT entered Indonesia for the first time in 1989 along with the emergence of private banks that really needed an online communication system such as an ATM (Automated Teller Machine). The use of VSAT in Indonesia is one of the first in Southeast Asia, which was pioneered by a national private company PT Citra Sari Makmur (CSM) with a PT TELKOM license. CSM began operating in early 1990 by utilizing the PALAPA satellite. Currently, apart from CSM, there are 3 private VSAT operators, namely Lintasarta, Elektrindo Nusantara and Rintis Sejahtera (Primacom). The largest market share is still controlled by CSM. Apart from that there are still 2 operators that only serve their own people, Dwi Mitra (Garuda Indonesia group) and BMG (Meteorology and Geophysics Agency).